Comparative economic evaluation of quetiapine plus lamotrigine combination vs quetiapine monotherapy (and folic acid vs placebo) in patients with bipolar depression (CEQUEL). (17th December 2018) - Simon, Judit; Geddes, John R.; Gardiner, Alexandra; Rendell, Jennifer; Goodwin, Guy M.; Mayer, Susanne
Abstract: Objectives: Although not licensed for acute bipolar depression, lamotrigine has evidence for efficacy in trials and its use is recommended in guidelines. So far there had been no prospective health economic evaluation of its use. Methods: Cost‐utility analysis of the CEQUEL trial comparing quetiapine plus lamotrigine vs quetiapine monotherapy (and folic acid vs placebo in an add‐on factorial design) for patients with bipolar depression (n = 201) from the health and social care perspective. Differences in costs together with quality‐adjusted life years (QALYs) between the groups were assessed over 52 weeks using a regression‐based approach. Results: Health‐related quality of life improved substantially for all randomization groups during follow‐up with no significant difference in QALYs between any of the comparisons (mean adjusted QALY difference: lamotrigine vs placebo −0.001 (95% CI: −0.05 to 0.05), folic acid vs placebo 0.002 (95% CI: −0.05 to 0.05)). While medication costs in the lamotrigine group were higher than in the placebo group (£647, P < 0.001), mental health community/outpatient costs were significantly lower (−£670, P < 0.001). Mean total costs were similar in the groups (−£180, P = 0.913). Conclusions: Lamotrigine improved clinical ratings in bipolar depression compared with placebo. This differential effect was not detected using the EQ‐5D‐3L. The additional cost of lamotrigine was balanced by significant savings in some other medical costs which made its use cost neutral to the health service. Compared to placebo, folic acid produced neither clinical nor significant health economic benefits. The study supports the use of lamotrigine in combination with other drugs to treat bipolar depression.